Industrial applications of green solvents. - Inamuddin (Materials research foundations ;, 2019)
The book focuses on new applications of green solvents (water, ionic liquids, supercritical carbon dioxide, terpenes). Keywords: Green Chemistry, Pollution Control, Hazardous Waste, Environmental Pollution, Green Solvents, Ionic Liquids, Supercritical Carbon Dioxide, Terpenes, Chemical Synthesis, Lipase-catalyzed Reactions, Organic Synthesis, Esterification, Gas Separation Membranes, Environment-friendly Products, Low Energy Requirement Processes, Alternatives to Hazardous Substances, Spiroheterocycles in Water, Sustainable Organic Synthesis, Chemical Industry, Pharmaceutical Industry, Paint I.